2014
DOI: 10.1186/1742-9994-11-13
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, environmental requirements, and biogeography of bivalve wood-borers (Teredinidae) in European coastal waters

Abstract: BackgroundBivalve teredinids inflict great destruction to wooden maritime structures. Yet no comprehensive study was ever carried out on these organisms in European coastal waters. Thus, the aims of this study were to: investigate the diversity of teredinids in European coastal waters; map their past and recent distributions to detect range expansion or contraction; determine salinity-temperature (S-T) requirements of species; flag, for future monitoring, the species that pose the greatest hazard for wooden st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 26 publications
2
67
1
3
Order By: Relevance
“…As espécies com larvas lecitotróficas apresentam período de vida planctônica mais curto que as planctotróficas e têm geralmente maiores chances de sucesso reprodutivo. Em função disso, geralmente são as mais abundantes (Turner, 1966;Borges et al, 2014). No entanto, o número de indivíduos de L. floridanus, única espécie com larvas lecitotróficas encontrada, foi pequeno quando comparado ao das espécies com larvas planctotróficas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As espécies com larvas lecitotróficas apresentam período de vida planctônica mais curto que as planctotróficas e têm geralmente maiores chances de sucesso reprodutivo. Em função disso, geralmente são as mais abundantes (Turner, 1966;Borges et al, 2014). No entanto, o número de indivíduos de L. floridanus, única espécie com larvas lecitotróficas encontrada, foi pequeno quando comparado ao das espécies com larvas planctotróficas.…”
Section: Discussionunclassified
“…Os Teredinidae são bivalves especializados na perfuração e digestão de madeira, ocorrendo, predominantemente, em ambiente marinho e de água salobra de regiões temperadas e tropicais, embora algumas espécies possam ocorrer em águas mais frias ou em salinidades próximas a zero (Turner, 1966;Borges et al, 2014). São animais de grande importância econômica e ecológica, pois aceleram a degradação de estruturas de madeira, contribuindo para a reciclagem mais rápida dos macrodetritos vegetais (roBerTson, 1991).…”
unclassified
See 1 more Smart Citation
“…Among others, the occurrence of T. bartschi was reported from the mangroves in Mamanguape estuarine region of the north-eastern Brazil by Leonel et al 4 and the presence of B. rochi and L. pedicellatus in the mangrove habitats of the Burrup peninsula in Western Australia by Brearley et al 5 Like-wise, Beasley et al 30 identified the presence of L. pedicellatus and Teredo spp. from Ajuruteua Peninsula of northern Brazil while Borges et al 11 recognized the incidence of L. pedicellatus in the Tagus Estuary, Borges et al 31 found the occurrence of B. carinata, L. pedicellatus and T. bartschi in European coastal waters.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to improve `taxonomic resolution´ in this species complex because many studies rely on taxonomic precision. Examples include studies of species diversity, one of the most widely adopted measures of biodiversity (Chiarucci et al 2011), biogeography (Borges et al 2014a) and bioassessment (Lenat and Resh 2001;Chessman et al 2007). …”
Section: Introductionmentioning
confidence: 99%